The fatigued anesthesiologist: A threat to patient safety? - Ashish Sinha; Avtar Singh; Anurag Tewari (Wolters Kluwer Medknow Publications, 2013)
Universally, anesthesiologists are expected to be knowledgeable, astutely responding to clinical challenges while maintaining a prolonged vigilance for administration of safe anesthesia and critical care. A fatigued anesthesiologist is the consequence of cumulative acuity, manifesting as decreased motor and cognitive powers. This results in impaired judgement, late and inadequate responses to clinical changes, poor communication and inadequate record keeping. With rising expectations and increased medico-legal claims, anesthesiologists work round the clock to provide efficient and timely services, but are the "sleep provider" in a sleep debt them self? Is it the right time to promptly address these issues so that we prevent silent perpetuation of problems pertinent to anesthesiologist's health and the profession. The implications of sleep debt on patient safety are profound and preventive strategies are quintessential. Anesthesiology governing bodies must ensure requisite laws to prevent the adverse outcomes of sleep debt before patient care is compromised.